A little boy lost : together with the poems of W. H. Hudson. - Hudson, W. H. (William Henry), 1841-1922. (New York : AMS Press, 1968)
Relates a little boy's many strange adventures when he wanders too far from home and becomes lost.
Keywords: Fantasy; English poetry